Hypoxia specifically induces CADM3 expression in pulmonary endothelial cells and promotes monocyte adhesion - MENG Xiangqiong; MENG Xiangqiong; CHEN Ting; CHEN Ting (陆军军医大学学报)
Objective‍　‍To investigate the expression profile of cell adhesion molecular 3 （CADM3） on pulmonary endothelial cells， analyze its role in mediating specific adhesion to monocyte， and explore a new mechanism of hypoxia inducing peripheral monocyte infiltration in pulmonary vessels. Methods‍　‍Human umbilical vein endothelial cells （HUVEC）， rat pulmonary vascular endothelial cells （rPEC）， and rat aortic endothelial cells （rAEC） were subjected， and divided into normoxic （21%O2） control group and hypoxic （1%O2 or 5%O2） treatment group. Analyzing the transcriptome data of HUVEC exposure to hypoxia for 8 h screened a differentially expressed molecule， CADM3. Cell adhesion experiments， siRNA interference， immunohistochemical assay， Western blotting， and flow cytometry were used to study the role of CADM3 in hypoxia specific high adhesion of HUVEC monocytes. Iron chelator deferoxamine （DFX） and shRNA interference were employed to enhance the expression of HIF-1α， and the effect of HIF-1 transcriptional activity on CADM3 expression was analyzed. Results‍　‍Hypoxic treatment resulted in enhanced expression of CADM3 in HUVEC， and the expression level reached the peak at 6-8 h after hypoxia， and then decreased. Transfection with siRNA targeting CADM3 decreased the expression of CADM3， and significantly reduced the adhesion rate of hypoxic HUVEC-U937 cells when compared with the negative control group （P<0.05）. Compared with the solvent control group， the protein levels of HIF-1α and its target protein STC2 in HUVEC treated with DFX （100 μmol/L） were increased. Transfection with shRNA targeting HIF-1α led the protein levels of HIF-1α and its target protein STC2 decreased， but had no effect on the protein expression of CADM3 in comparison to the negative control group. The protein level and distribution of CADM3 on the cell membrane were increased in hypoxic rPEC. No expression of CADM3 protein was found in the rAEC when compared with rPEC. After treatment with 5 μg/mL LPS， there were no significant changes in HIF-1α， STC2 and CADM3 in rPEC cultured under normoxia or hypoxia. The adhesion rate between hypoxia rPEC with CD11b+ cells was the highest， with statistical significance （P<0.01）. After incubation with anti-CADM3 antibody， the adhesion of hypoxic rPEC-U937 was significantly decreased compared with the solvent control group （P<0.05）. Conclusion‍　‍Hypoxia specifically induces the expression of CADM3 in pulmonary vascular endothelial cells in a HIF-1-independent manner， and promotes the specific adhesion of pulmonary vascular endothelial cells and monocytes induced by hypoxia.